Pengaruh Nilai Taksiran, Reputasi, dan Promosi terhadap Keputusan Pembelian Emas Batangan (Logam Mulia) di PT. Pegadaian Cabang Nagoya Batam - Jefri Idayat; Yandra Rivaldo; Jeffi Mutiara (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2026)
This study aims to analyze the influence of perceived appraisal value, reputation, and promotion on the purchase decision of gold bars (precious metals) at PT Pegadaian Nagoya Branch, Batam. The phenomenon underlying this research is the fluctuation in the number of gold bar transactions for the 2023–2025 period and customers' hesitation in determining the purchase timing, along with the tendency to compare with other providers. The research methodology uses a quantitative approach with purposive sampling, involving 75 respondents who are active customers. Data were collected through questionnaires and analyzed using multiple linear regression with SPSS software. The partial results show that appraisal value has a positive influence of 26.7%, reputation 29.7%, and promotion 34.7% on purchase decisions. Simultaneously, these three variables significantly influence and strengthen customers' purchase decisions. These findings indicate that transparency in appraisal values, strengthening corporate image, and informative promotional strategies are key to increasing gold transaction volumes. This research provides practical contributions for PT Pegadaian in designing more effective marketing strategies to face competition in the gold investment market.